Diagnostic analysis of baseline brain MRI features in infants with congenital cytomegalovirus infection: a simplified scoring system. Issue 12 (December 2021) - Kachramanoglou, C.; Jan, W.; Jones, B.; Papachatzi, E.; Zombori, L.; Khan, F.; Gaur, P.; Basheer, N.; Randell, P.; Lyall, H.
Abstract : AIM: To characterise the magnetic resonance imaging (MRI) features of infants with congenital cytomegalovirus (CMV) and categorise those into a simplified MRI scoring system. MATERIALS AND METHODS: Three neuroradiologists reviewed the examinations of 71 infants retrospectively and scored for the presence of a white matter signal abnormality and structural lesion and each MRI was given a score of 0, 1, 2, or 3 for normal, structural abnormality alone, white matter abnormality alone, white matter abnormality plus structural lesion, respectively. Imaging features were outlines according to symptomatology. Chi-square and Spearman's rho were used to test relationships between MRI features and viral loads and MRI score/symptomatic disease respectively. Cohen's Kappa coefficient was used to assess interobserver agreement. RESULTS: Of the 49 abnormal studies, 40% ( n= 20) were seen in asymptomatic infants. The commonest finding was white matter signal abnormality, followed by cyst formation and polymicrogyria (86%, n= 42; 71%, n= 35; and 33%, n= 16, respectively). Cysts were significantly positively correlated with white matter abnormalities and polymicrogyria. On the MRI score, 31%, 10%, 15%, and 44% obtained a score of 0, 1, 2, and 3, respectively; the MRI score was positively correlated with log-transformed viral loads. Interobserver agreement for the presence of white matter signal abnormality, cyst formation, malformations of cortical development (MCD), and global MRI score was excellent (k = 0.82, 0.94, 0.96, and 0.86, respectively). CONCLUSION: Baseline MRI provides information valuable for treatment decisions, especially in "asymptomatic" infants. The simplified scoring system is easier to use, incorporating solely the imaging findings that are anticipated to have an effect on clinical outcome. Highlights: White matter signal abnormality is the most common finding in cCMV. Our simplified scoring, based on MR features alone, proved highly reliable. White matter change, cyst and polymicrogyria are only incorporated in the score.